1976
DOI: 10.1001/archpedi.1976.02120050038006
|View full text |Cite
|
Sign up to set email alerts
|

Mania in Childhood

Abstract: Criteria for mania in children have been established on the basis of criteria for mania in adults. Mania in children is an episodic disorder characterized by marked irritability and agitation, a considerable increase in activity level, push of speech, sleep disturbances, distractability, and noticeable mood instability that persists for longer than one month. Euphoria is frequently present in children with mania and is manifested as an adamant denial of any illness or problem. Previous reports have not stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…O'Connell et al (17) found a high incidence of mood disturbance, socio pathy, and maladjustment during interviews with the offspring of lithium-responding manicdepressive probands. Amtell (3) reported a simi lar broad range of mood and behavioral symp toms in her manic child patients as did Wein berg and Bmmback (23) in their study of 5 manic children. Waters (22) in his extensive review of risk factors in bipolar illness, points out tlrat because of methodological flaws, studies of children of bipolar patients have failed to show any homologous behavioral ante cedents to the later development of their own bipolar disease.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…O'Connell et al (17) found a high incidence of mood disturbance, socio pathy, and maladjustment during interviews with the offspring of lithium-responding manicdepressive probands. Amtell (3) reported a simi lar broad range of mood and behavioral symp toms in her manic child patients as did Wein berg and Bmmback (23) in their study of 5 manic children. Waters (22) in his extensive review of risk factors in bipolar illness, points out tlrat because of methodological flaws, studies of children of bipolar patients have failed to show any homologous behavioral ante cedents to the later development of their own bipolar disease.…”
Section: Discussionmentioning
confidence: 90%
“…Puig-Antich et al (18) and Cytryn and McKandrew (7) found strong family histories of the depressive illness in the background of their latency in agedepressed children and Weinberg and Brumback (23) found histories of depression in the par ents of their manic patients. Again the relative ly young mean age of our offspring population may be a factor in explaining the absence of more formal psychiatric illness in this popula tion of offspring.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of its original description, child psychiatry was extensively influenced by psychoanalytic concepts according to which young children were precluded from a diagnosis of depression (and hence of manic disorder) because their superego was not sufficiently developed. Depression in childhood is now extensively acknowledged (Rutter and Garmezy, 1983) and mania has been described and reviewed by Weinberg and Brumback (1976). The phenomenological similarity between childhood mania and hyperkinesis is compelling (Table 2).…”
Section: Hypomania and Maniamentioning
confidence: 99%
“…For example, Weinberg and Brumback [20] created criteria to diagnose mania in children. These criteria, which included symptoms of euphoric or irritable mood, hyperactive behavior, and flight of ideas, served as the basis for the DSM-III bipolar disorder criteria.…”
Section: History Of Bipolar Disordermentioning
confidence: 99%